INVESTOR LEGAL PROTECTION IN THE INDONESIAN INDUSTRIAL 4.0 - Wahyudi, Wahyudi (Tadulako University, 2019)
Industry 4.0 its a combination of automation technology and cyber technology that is inevitable especially for the advancement of industry in Indonesia. The hospitality of foreign investment is very necessary for investors to invest in Indonesia, especially the existence of legal protection for security of investments in the framework of industrial development 4.0. The form of legal protection provided by the Government of Indonesia is with various kinds of regulations that support foreign investment, one of which is Constitution Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, Constitution Number 25 of 2007 concerning Investment and Comunication Ministerial Regulations No 20 of 2016 concerning Protection of Personal Data and the existence of a Personal Data Protection legislation.